STRUKTURAL FUNGSIONAL SISTEM PEMBELAJARAN DI MASA PANDEMI COVID-19 - Qurrota A'yun (UNIVERSITAS SEBELAS MARET (UNS), 2022)
The Covid-19 pandemic has brought about changes in various aspects of people's lives, one of which is education. Previously, the learning system carried out face-to-face at schools or campuses had to be changed to virtual meetings at home since the Covid-19 pandemic. This is done so that the learning process continues. Based on this phenomenon, this study aims to examine the learning system during the Covid-19 pandemic according to Talcott Parsons' structural-functional perspective. The research uses qualitative research with a literature study approach. The results of the study show that changes in the learning system during the pandemic are reviewed with Talcott Parsons' functional structural theory through the AGIL function, namely: (1) Adaptation, the learning system that was originally carried out face-to-face is transferred at home via online or virtual meetings. (2) Goal Attainment, an online learning system is implemented so that teaching and learning activities can be carried out so that students and students still get their right to obtain education and develop their potential even during the Covid-19 pandemic. (3) Integration, the government, namely the Ministry of Education and Culture, and the school or campus must cooperate by making a policy that can help students and students in online learning. One of the policies made is internet quota assistance for students throughout Indonesia. (4) Latency, students and students must maintain the values of discipline even though the learning process is not carried out in schools or campuses.Keywords: Education, Covid-19 pandemic, change, learning system AbstrakPandemi Covid-19 membawa dampak perubahan dalam berbagai aspek kehidupan masyarakat salah satunya aspek pendidikan. Sebelumnya, sistem pembelajaran dilakukan secara tatap muka di sekolah atau kampus harus diubah menjadi virtual meeting di rumah semenjak adanya pandemi Covid-19. Hal ini dilakukan agar proses pembelajaran tetap terlaksana. Berdasarkan fenomena tersebut, penelitian ini bertujuan untuk mengkaji sistem pembelajaran di masa pandemi Covid-19 menurut perspektif struktural fungsional Talcott Parsons. Penelitian menggunakan penelitian kualitatif dengan pendekatan studi pustaka. Hasil penelitian menujukkan bahwa perubahan sistem pembelajaran di masa pandemi ditinjau dengan teori struktural fungsional Talcott Parsons melalui fungsi AGIL yaitu: (1) Adaptation, sistem pembelajaran yang semula dilakukan secara bertatap muka dialihkan di rumah secara daring atau virtual meeting. (2) Goal Attainment, sitem pembelajaran daring diterapkan agar aktivitas belajar-mengajar dapat terlaksana sehingga siswa-siswi dan mahasiswa tetap mendapatkan hak nya untuk memperoleh pendidikan dan mengembangkan potensi mereka meskipun di masa pandemi Covid-19. (3) Integration, pemerintah yakni Kementerian Pendidikan dan Kebudayaan dan pihak sekolah atau kampus harus bekerjasama dengan membuat suatu kebijakan yang dapat membantu siswa-siswi dan mahasiswa dalam pembelajaran daring. Salah satu kebijakan yang dibuat adalah bantuan kuota internet untuk mahasiswa di seluruh Indonesia. (4) Latency, para siswa dan mahasiswa harus mempertahankan nilai-nilai kedisiplinan meskipun proses pembelajaran tidak dilaksanakan di sekolah atau kampus.Kata Kunci: Pendidikan, pandemi Covid-19, perubahan, sistem pembelajaran